Extending the theory of planned behavior: factors fostering millennials' intention to purchase eco-sustainable products in an emerging market - Lavuri, Rambabu (Journal of environmental planning and management, 2022)
Based on the Theory of Planned Behavior model, this exploratory study aims to examine factors fostering millennials' purchasing intentions toward eco-sustainable products in emerging markets and assess the interrelationship between environmental knowledge, environmental concern, subjective norms, green attitude, and perceived behavior. Data was collected from 446 Indian millennials using convenience sampling. The data were analyzed using the IBM SPSS and AMOS package using exploratory factor analysis, confirmatory factor analysis, and Structural Equation Modeling. The results revealed that environment knowledge, environmental concern, subjective norms, and perceived behavior factors significantly fostered green attitude. Millennial green attitude positively affected purchase intention and influenced millennials' purchase behavior both directly and indirectly. The study variables had a positive interrelationship, except for subjective norms and perceived behavior. Environmental knowledge and environmental concerns were the strongest determinants of GPI toward GPB.